Pembangunan titik kawalan ukur artileri untuk peta versi terhad - Ibrahim Yasir (Tesis, 2019)
The aim of this research is to develop the Artillery Survey Control Points (ASCP) so that three important initial data to execute the RAR operation, namely orientation, location, and elevation (OLE) can be develop for this Limited Version Map. This research has used the Multi Methodology Research that is Multiple Case Studies, Action Studies and Triangulation Methods in order to achieve three set of objectives. This research concludes that the Survey Section is often delayed completing the artillery survey success is due to the difficulty of obtaining accurate OLE data to execute the survey process.